Realgar transforming solution as a novel arsenic agent with a lower risk of cardiotoxicity - Yang Hai; Peng Song; Xin Wang; Longhe Zhao; Qinjian Xie; Jianyin Li; Yang Li; Hongyu Li (Elsevier, 2019)
QTc prolongation has been observed during arsenic trioxide and realgar's clinical use, and become a huge obstacle for the application. Our lab has obtained the soluble arsenic from realgar named realgar transforming solution or RTS. In this study, we first evaluated the cytotoxicity on NB4 cell and found that RTS could remarkably inhibit proliferation of NB4 than arsenic trioxide. Then we figured out the QTc prolongation of RTS treatment contrasted with arsenic trioxide; results revealed that arsenic trioxide prolonged corrected QTc of mice by 20.1% and showed 1.9-fold higher cytotoxicity on H9c2 cell than RTS. On the contrary, there could not find any QTc prolongation of mice in RTS treatment. Also, arsenic trioxide elevated the intercellular calcium accumulation of H9c2 cell by 2.02-fold v.s control and RTS. HE staining and Masson's trichrome staining had shown that there was no injured section after RTS treatments. IK1 currents of rat ventricular cardiomyocytes were diminished by 45.0% after treating with arsenic trioxide while RTS showed no significance than the control group. The results above indicated that RTS could serve as an alternative arsenic agent on leukemia and had a lower risk of cardiotoxicity. Keywords: Arsenic, Cardiotoxicity, RTS, ATO, Realgar